Russian Foreign Ministry and the Reorganization of Russian Orthodox Churches Abroad in 1860-s - V. O. Pechatnov (MGIMO University Press, 2020)
Based on the unearthed documents from the Archive of Foreign Policy of the Russian Empire, the article examines an interaction of Russian diplomacy and Russian orthodox churches abroad in the process of their reform in the early 1860-s. This reorganization was undertaken in context of the “Great reforms” of Alexander II and aimed at rationalization of the previous system of subordination of those churches to civil and ecclesiastical authorities in St. Petersburg. The architects of the reform initiated by the Tzar himself sought to create a unified system of subordination and financing of those churches with identical criteria for their personnel, their rights and duties vis-à-vis heads of diplomatic missions. Accordingly, the Russian Foreign Ministry became responsible for their operation and financing while in ecclesiastical matters they were to answer to the Holy Synod. Foreign Ministry and personally Alexander Gorchakov, as demonstrated in the article, played a leading role in the reform preparation and implementation conducted on an inter-agency basis with the Holy Synod, Ministry of the Court and Finance Ministry taking part. The heads of diplomatic missions and of the affiliated churches were also consulted in the process. The authors trace all stages of these complex negotiations that resulted in achieving a balance of interests between all the actors involved. The newly created system proved to be quite efficient and lasted till the end of the Russian empire. The reorganization revealed a state of the churches abroad and their clergy that was a crème of Russian Orthodox Church. The reform experience is also instructive as a case study of Russian government apparatus in action.